2021
DOI: 10.1101/2021.04.30.442182
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LY-CoV1404 (bebtelovimab) potently neutralizes SARS-CoV-2 variants

Abstract: LY-CoV1404 is a highly potent, neutralizing, SARS-CoV-2 spike glycoprotein receptor binding domain (RBD)-specific antibody identified from a convalescent COVID-19 patient approximately 60 days after symptom onset. In pseudovirus studies, LY-CoV1404 retains potent neutralizing activity against numerous variants including B.1.1.7, B.1.351, B.1.427/B.1.429, P.1, and B.1.526 and binds to these variants in the presence of their underlying RBD mutations (which include K417N, L452R, E484K, and N501Y). LY-CoV1404 also… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 79 publications
3
96
0
Order By: Relevance
“…well as the structure of antibody COV2-2130 in complex with the SARS-CoV-2 RBD (Table S2). The results revealed significant positive correlations with only six other antibodies: REGN10987 (Hansen et al, 2020), 2-7 (Liu et al, 2020), C119 (Barnes et al, 2020), COVOX-75 (Dejnirattisai et al, 2021), COV2-2130 (Zost et al, 2020) (in agreement with the observed binding competition with 54042-4, Figure 2D), and LY-CoV1404 (Westendorf et al, 2021) (Figure 4B). However, of these six antibodies, COVOX-75 has been reported as not a potent neutralizer (Dejnirattisai et al, 2021).…”
Section: -4 Binds the Apex Of The Sars-cov-2 Rbd In The Down Conformationsupporting
confidence: 80%
See 1 more Smart Citation
“…well as the structure of antibody COV2-2130 in complex with the SARS-CoV-2 RBD (Table S2). The results revealed significant positive correlations with only six other antibodies: REGN10987 (Hansen et al, 2020), 2-7 (Liu et al, 2020), C119 (Barnes et al, 2020), COVOX-75 (Dejnirattisai et al, 2021), COV2-2130 (Zost et al, 2020) (in agreement with the observed binding competition with 54042-4, Figure 2D), and LY-CoV1404 (Westendorf et al, 2021) (Figure 4B). However, of these six antibodies, COVOX-75 has been reported as not a potent neutralizer (Dejnirattisai et al, 2021).…”
Section: -4 Binds the Apex Of The Sars-cov-2 Rbd In The Down Conformationsupporting
confidence: 80%
“…Here, we report the identification of 54042-4, an antibody that exhibited potent SARS-CoV-2 neutralization against USA-WA1 as well as the currently circulating Alpha, Beta, Gamma, and Delta VOCs. Interestingly, antibody 54042-4 neutralized virus at comparable IC 50 s to the clinical candidates LY-CoV1404 and REGN10987, despite having $10-fold lower affinity for the RBD (Hansen et al, 2020;Westendorf et al, 2021). Although the epitope of antibody 54042-4 showed partial overlap with that of several other known RBD-directed antibodies, our findings revealed a distinct mode of SARS-CoV-2 spike recognition, paired with an uncommon genetic signature that distinguishes 54042-4 from other SARS-CoV-2 antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, combination therapies comprising a cocktail of NAbs targeting distinct nonoverlapping epitopes on RBD have demonstrated exceptional potency and promising correlates of protection against SARS-CoV-2 and its variants (Fig 2B) [36,38]. Additionally, newly identified RBD core-binding NAbs SARS2-38 [39] and LY-CoV1404 [40] as monotherapy potently neutralize all SARS-CoV-2 VOCs. Therefore, several options of NAbs targeting conserved RBD epitopes are emerging as promising and attractive therapeutic candidates to tackle the disease burden caused by SARS-CoV-2 or its variants.…”
Section: What Is the Efficacy Of Sars-cov-2 Mabs Against Emerging Variants?mentioning
confidence: 99%
“…The inclusion of a universally acceptable robust positive control is essential in the evolving serological/neutralization assays for SARS-CoV-2. A recent report suggested potent neutralization of SARS-CoV-2 variants by an antibody, LY-CoV1404 [40]. However, as it is not commercially available to researchers for assay harmonization, we used NIBSC 20/130 reagent as a positive control.…”
Section: Discussionmentioning
confidence: 99%